ASSESSMENT OF THE FEASIBILITY OF AKU SMALL HYDROPOWER PROJECT USING RETSCREEN ENERGY MODEL SOFTWARE (Nigerian Journal of Technology, 2024)
AbstractThe RETScreen 4 software was used in this study to conduct the analysis to determine the viability of the river Aku hydropower plant in Uturu, Abia State. The study was carried out using data from Ivo river dam authority, previous studies and literatures. The result of the study showed that the Aku river could generate an annual energy of 6,434,000kWh and will be able to payback its project cost at 6.3 years. The estimated annual GHG reduction of the project stood at 4,310.7tCo2 an equivalent of 1,852,317 litres of gasoline not used. The sensitivity/risk analysis indicated that electricity export rate (electricity sales price), initial cost and debt interest rate impacted the project profitability the most in that order. The project NPV is sensitive to both the debt interest rate and the initial cost of the project as variation in cost above 30% will throw the project into a negative NPV. In the light of the available information, the project is feasible if implemented.